2009
DOI: 10.1038/jid.2009.16
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Targeting of cFLIP Sensitizes Activated T Cells to Undergo Apoptosis and Desensitizes Responses to Contact Dermatitis

Abstract: Contact dermatitis is the result of inflammatory responses mediated by hapten-specific activated CD8+ and CD4+ T cells. Activation-induced cell death (AICD) is a naturally occurring process regulating the resolution of T-cell responses through decreased expression of the antiapoptotic molecule cellular FLICE inhibitory protein (cFLIP). We show that targeting cFLIP expression in vitro and in vivo, with morpholino antisense applied systemically or topically in conjunction with antigen, sensitizes T cells to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Among these is the antisense targeting of EBOV VP35 protein expression, which provided significant protection against lethal challenge. Important to the studies shown here is the capability of a PPMO to deliver antisense into murine leukocytes, both in vitro and in vivo (Marshall et al, 2007;Mourich et al, 2009). The ability to target protein expression in vivo with PPMOs make these particularly useful agents for determining the role of different host immune factors in the pathogenesis of EBOV.…”
Section: Resultsmentioning
confidence: 97%
“…Among these is the antisense targeting of EBOV VP35 protein expression, which provided significant protection against lethal challenge. Important to the studies shown here is the capability of a PPMO to deliver antisense into murine leukocytes, both in vitro and in vivo (Marshall et al, 2007;Mourich et al, 2009). The ability to target protein expression in vivo with PPMOs make these particularly useful agents for determining the role of different host immune factors in the pathogenesis of EBOV.…”
Section: Resultsmentioning
confidence: 97%
“… 36 , 37 For anti c-FLIP morpholinos, positions in the 5′-UTR and near the AUG start codon have been described as efficient target sites. 38 PNA1–4 conjugates are complementary to different targets around the start codon (−30 to 15, −13 to 3, −5 to 11, and −1 to 15, relative to the start codon). For comparison, we included PNA5 , which is designed to bind within the ISIS 23296 target segment in the c-FLIP coding region.…”
Section: Resultsmentioning
confidence: 99%
“…ISIS 23296 is an optimized oligophosphorothioate gapmer sequence, which induces RNAs H. Antisense PNAs hinder mRNA translation by steric blockage . Literature evidence suggests that inhibition of protein synthesis by steric block antisense compounds such as PNA, morpholino nucleic acids, and 2′-OMe-RNA occurs more effectively near the site of translation initiation rather than in the coding region targeted by ISIS 23296, indicating that interfering with ribosome assembly is easier than perturbing elongation. , For anti c-FLIP morpholinos, positions in the 5′-UTR and near the AUG start codon have been described as efficient target sites …”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of the FADD adapter protein in cultured RA synoviocytes induced apoptosis in these cells, and in a xenograft mouse model of proliferating rheumatoid synovium, ectopic expression of FADD through retroviral transduction lead to a significant reduction of synoviocytes and mononuclear cells 75 . Reducing levels of c-FLIP, another molecule that regulates Fas signaling has been shown to sensitize fibroblast-like synoviocytes from RA patients to Fas-induced apoptosis and sensitized T cells to TCR-induced apoptosis 76,77 . Indirect targeting of Fas through its ligand is another plausible therapeutic mechanism.…”
Section: Targeting Fas and Other Death Receptors In Rheumatic Diseasesmentioning
confidence: 99%